Assessing digital financial inclusion and financial crises: The role of financial development in shielding against shocks - Huy Nguyen Quoc; Dinh Le Quoc; Hai Nguyen Van (Heliyon)
Digital financial inclusion (DFI) has been proven to be a central factor in driving economic development and reducing inequality in countries. However, its impact on financial crises (FC) has yet to be clearly examined, particularly in the context of current Financial Development (FD). Therefore, this study examines the influence of DFI on FC across 52 countries from 2004 to 2020, focusing on how this impact varies with the level of FD. Using a combination of Threshold Regression (PTR) and Bayesian regression methods, the research first identifies structural breaks in the DFI-FC relationship, with FD as the threshold variable. Bayesian regression is then employed to address challenges such as small sample sizes, endogeneity, and autocorrelation, while assessing DFI's differential impact across countries with varying FD levels. The PTR analysis reveals a threshold value of 0.6036, indicating a non-linear DFI-FC relationship depending on FD levels. In low FD countries, DFI reduces the risk of FC, whereas in high FD countries, uncontrolled DFI increases it. Based on the results, we suggest that financial institutions should strengthen efforts to promote investment in digital technology by implementing digital skills training programs, providing capital to businesses and individuals, and facilitating support from financial institutions in countries with low FD. Meanwhile, for countries with high FD, regulatory authorities should establish stricter regulations and supervision mechanisms for digital financial activities to mitigate the risks of FC.